Remittances and Financial Deepening in Nepal - Bhandari, Suresh Singh (Journal of Durgalaxmi, 2023)
In the case of remarkable remittance inflows, the impact of remittances on financial development in Nepal has not been adequately studied. Therefore, this paper investigates the effects of remittances on financial development, using Nepal as a case study for the period from 1975 to 2021. The study examines the impact of remittances on the broad money supply. Alongside remittances as the key explanatory variable, other control explanatory variables such as gross capital formation, total trade, real gross domestic product, the national consumer price index, and foreign aid were considered. Unit root analysis revealed that all variables were integrated at order one. Consequently, a cointegration test was conducted, indicating the presence of at least one cointegration equation. Subsequently, an ordinary least squares regression was performed using the first difference data. The results were subjected to various econometric diagnostic tests, including assessment for autocorrelation, heteroscedasticity, multicollinearity, normality, as well as the Durbin–Watson test, t-tests for coefficients, and the F-test. Both the coefficient of determination and the adjusted coefficient of determination confirmed that the models were well-fitted. The outcomes of the model suggest that remittances have a positive impact on the enhancement of the broad money supply. Based on these findings, the study recommends implementing policies aimed at boosting remittance inflows into the country to further financial development in Nepal, specifically promoting financial deepening.